Osteometría y genética de los camélidos mochica, costa norte del Perú - Víctor F. Vásquez Sánchez; Teresa Rosales Tham (Revista del Museo de Antropologia, 2009)
The objective of this study was to evaluate the results of osteometric analyses applied to camelid bones samples from Moche sites (I and VII AD) located on the north coast of Peru. The bones analyzed in this study correspond to first phalanges from two Moche archaeological sites (Cerro Chepén and Moche Urban Zone). Discriminant analysis was conducted on a sample of 44 first phalanges, taking into account five measurments in each bone. The results showed the identification in both sites of two species of domestic camelids, Lama glama “llama” and Lama pacos“alpaca.” The interpretation of the results is discussed by explaining a model of geographic or vicariant speciation of camelids that inhabited the coast of Peru during Moche times. This model takes into account that in this environment currently camelids are not breed, as well as genetics and evolutionary factors in the new domestic form, the effect of Bergmann’s Rule, and new grasses in the morphology of this new form of domestic camelid, ,which lived in the region at the time of Moche.